1999
DOI: 10.1212/wnl.52.7.1422
|View full text |Cite
|
Sign up to set email alerts
|

123 I-IPT brain SPECT study in essential tremor and Parkinson’s disease

Abstract: Later in their clinical courses, some patients with postural tremor may acquire rest tremor in association with mild substantia nigra neuronal loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 28 publications
4
49
0
2
Order By: Relevance
“…28 Evidence of nigrostriatal deficiency in ET has been reported by some studies. [29][30][31] A 10% to 13% reduction in 18F-dopa uptake in the striatum of patients with ET compared to controls suggests a physiologically important compromise of the dopaminergic system in ET patients. 32 According to a theory proposed by Morilak and Frazer, behavioral functions such as ''loss of energy", and ''apathy" may be linked to a reduced dopaminergic activity.…”
Section: Discussionmentioning
confidence: 99%
“…28 Evidence of nigrostriatal deficiency in ET has been reported by some studies. [29][30][31] A 10% to 13% reduction in 18F-dopa uptake in the striatum of patients with ET compared to controls suggests a physiologically important compromise of the dopaminergic system in ET patients. 32 According to a theory proposed by Morilak and Frazer, behavioral functions such as ''loss of energy", and ''apathy" may be linked to a reduced dopaminergic activity.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Lee et al [8] using 123 I-IPT SPECT and Schwarz et al [9] with 123 I-Ioflupane SPECT reported reduced striatal binding in essential tremor with clinical features suggestive for Parkinson's disease (i.e., isolated rest tremor and visual-motor coordination failure, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…123 I-Ioflupane striatal dopamine transporter binding is reported in the normal range in essential tremor: the tracer is registered in Europe for differential diagnosis with Parkinson's disease [7]. However, single photon computed emission tomography (SPECT) and positron emission tomography (PET) studies [5,8,9] suggested abnormalities in some essential tremor cases, with a possible link to positive family history.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a series of papers using SPECT imaging demonstrated that ET patients had mild abnormalities of striatal dopamine transporters and a significant presynaptic dopaminergic deficit [40,41] . Others have demonstrated that ET patients who develop isolated rest tremor have evidence on neuroimaging studies of mild nigral neuronal loss [42] and that there is evidence of reduced striatal volume in ET as well [43] . Therefore, the literature is somewhat mixed, with the central question being whether changes in the basal ganglia are a feature of a subgroup of patients who have bone fide ET or whether the 'ET' patients with these imaging abnormalities have a forme fruste of PD rather than ET.…”
Section: Biological Evidencementioning
confidence: 99%